PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN DALAM MEMILIH PRODUK (Studi Kasus pada Customer Baru MyDevTeam) - Ainun N, Fardhotun; Sari, Maheni Ika; Winahyu, Pawestri (Growth, 2022)
This study aims to determine and analyze the influence of marketing mix decisions in choosing a product (Case Study on New Customers in MyDevTeam). The primary data sources used in this study were respondents' answers through a questionnaire item. The population of this study is all new potential customers who make purchases at MyDevTeam. The number of samples in this study was set at 110 respondents with the criteria of prospective customers who have a business more than 1 year so that they need innovative marketing services. The analytical tool used in this research is multiple linear regression analysis. The results of multiple regression testing show that product quality influences the decision to choose a new customer product at MyDevTeam. Price affects the decision to choose a new customer product in MyDevTeam. Place affects the decision to choose a new customer product in MyDevTeam. Promotion affects the decision to choose a new customer product in MyDevTeam.